Artikel Penerapan Media Film (Direct Photography) Dalam Pembelajaran Haji Dan Umrah Untuk Siswa SMP - Elfi Kusrini (GHIROH, 2022)
This article was conducted with the aim of knowing the motivation and learning outcomes of students through the use of film media (Direct Photography) in class VII SMP. This research is a classroom action research. The subjects of this study were students of class IX SMP, amounting to 33 people. The research was conducted in 2 cycles. The results showed that the use of Media Film (Direct Photography) accompanied by a cooperative learning model in learning the procedures for Hajj and Umrah in class IX SMP was proven to significantly increase student motivation and learning outcomes. So that it can be used for the learning process in the future.